A Novel Combination of Serum Markers in a Multivariate Model to Help Triage Patients Into “Low-” and “High-Risk” Categories for Prostate Cancer - McNally, Christopher J.; Watt, Joanne; Kurth, Mary Jo; Lamont, John V.; Moore, Tara; Fitzgerald, Peter; Pandha, Hardev; McKenna, Declan J.; Ruddock, Mark W. (Frontiers in Oncology, 2022)
Background: Almost 50,000 men in the United Kingdom (UK) are diagnosed each year with prostate cancer (PCa). Secondary referrals for investigations rely on serum prostate-specific antigen (PSA) levels, and digital rectal examination (DRE). However, both tests lack sensitivity and specificity, resulting in unnecessary referrals to secondary care for costly and invasive biopsies. Materials and Methods: Serum samples and clinical information were collected from N=125 age-matched patients: n=61 non-PCa; n=64 PCa, and analysed using Biochip Array Technology (BAT) on high-sensitivity cytokine array I (IL-2, IL-4, IL-6, IL-8, IL-10, IL-1α, IL-1β, TNFα, MCP-1, INFγ, EGF and VEGF); cerebral array II (CRP, D-Dimer, NSE and sTNFR1) and tumour PSA oncology array (fPSA, tPSA and CEA). Results: Data showed 11/19 (68.8%) markers were significantly different between the non-PCa and PCa patients. A combination of EGF, log10 IL-8, log10 MCP-1, and log10 tPSA significantly improved the predictive potential of tPSA alone to identify patients with PCa (De Long p<0.001). This marker combination had an increased AUROC (0.860 vs. 0.700), sensitivity (78.7% vs. 68.9%), specificity (76.5% vs. 67.2%), PPV (76.2% vs. 66.7%) and NPV (79.0% vs. 69.4%) compared to tPSA. Conclusions: Single markers lack both sensitivity and specificity to stratify risk of PCa in patients who present with elevated tPSA and abnormal DRE. The novel combination of serum markers identified in this study could be employed to help triage patients into ‘low’ and ‘high’ risk categories, allowing general practitioners (GPs) to improve management of patients in primary care settings and potentially reducing the number of referrals for unnecessary, invasive, and costly treatments.